Estudo de viabilidade da piscicultura orgânica em uma unidade de produção familiar - Rossignol, Vera Maria (2021)
From the perspective of healthy food production, the objective of this work was to analyze the economic, financial, environmental and social feasibility of producing agroecological fish in ponds excavated in a family production unit. The specific objectives: Characterize how the production of agroecological fish can be developed in family farming; Assess the viability of organic fish production in family farming; Analyze environmental indicators and externalities of organic production. The development of the research occurs through semi-structured interviews applied to the farmer. The study analyzed in the period of sixteen months (December 2018 / March 2020), the production in polyculture system of organic fish. The adopted methodology is of exploratory descriptive character combining the bibliographic research with case study, with the study of the activity of the fish farm as well as to analyze the economic, environmental and social viability of the production, using the techniques and methods of analysis of economic viability: NPV, Payback, TIR, IL. The methods of valuing investments based on cash flow. The evaluation of the quality of the effluent generated in the polyculture system, in the nurseries, allows to analyze the production environmentally, demonstrating the positive use of the occupied area and the water used in the process. The work is organized in three stages, in the first, the introduction of the study. In the second stage, theoretical framework, which presents a section on the central theme of the work, a third stage in the form of an article, structured in three results: the first section of studies carried out on the economic and financial viability in organic agriculture. A second section related to the activity of authors on the economic and financial viability in fish farming. This study analyzed effluent externalities through the water quality parameters analyzed during the study period. The third discusses the case study that gave rise to this work, reporting the results obtained, and final considerations. The investment in the nurseries was budgeted at R $ 3,220.60. The sales value of the kg was estimated. species of fish produced. The cash flow balance was taken as the basis for the economic / financial feasibility analysis. However, the net present value of the projected cash flow was negative. Demonstrating that this investment does not increase the value of the initial investment. The realistic scenario the cash flow obtained shows the results with NPV <0 equal to -R $ 830.88, IRR of -23% less than TMA of 12%, in the same situation with negative NPV the data make fish production unfeasible in the optimistic scenario. From the income statement, it can be seen in the sixteen-month period that the activity has lower revenues than its initial investment and expenses. In the evaluation of the quality of the effluent generated in the nurseries, in the polyculture system, it allowed us to analyze the production environmentally, demonstrating the positive use of the occupied area and the water used in the process. The analysis of social viability, under the occupation of family labor, was found to be relevant in the phase of implantation of the nurseries, however in maintenance, the demand decreases, not being a significant income generator.